The Role of Modern Technologies in Spatial Analysis of Flash Flood Risk Sites: A Case Study of the Al-Abyar Area (Libya Journal of Geographical Studies, 2025)
In light of the natural challenges posed by flash floods, this study aims to identify and monitor areas threatened by flood risks in a major developmental region. The study relies on advanced hydrological techniques to simulate flash flood risks, thereby enhancing spatial analysis as one of the modern trends in geomorphology, where it is used for precise identification of areas exposed to such risks.The study also addresses the phenomenon of unplanned urban growth and its impact on flash flooding, utilizing modern technologies such as remote sensing and geographic information systems (GIS), which have proven effective in the study of urban geography, city planning, and management, including service distribution and efficiency, land use mapping, and the identification of informal settlements and deteriorating buildings.The study area includes the Al-Abyar Valley Basin, covering an area of 678 km², where an urban settlement has been established at the basin's outlet, making flash flooding a threat to urban development. The area has experienced several rainstorms in recent years, prompting the researcher to conduct a detailed study using one of these storms as a case study to assess the risk and determine its geospatial dimensions.This study aims to conduct a comprehensive analysis of the risks associated with flash flooding in the study area, including geomorphological and hydrological considerations, and to provide an accurate assessment of the natural and environmental conditions. The focus is on factors such as land leveling, natural terrain slope, and soil quality. It also presents recommendations to raise awareness of flash flood risks and applies several hydromorphological equations to identify sites threatened by flash flood risks.
Keywords: Flash Flooding; Geospatial Modeling; Hydrology; Geographic Information Systems (GIS)